THE EFFECT OF USING JOLLY PHONICS ON JORDANIAN FIRST GRADE PUPILS' READING - Abeer Nasrawi; Dina al-Jamal (Informascope, 2017)
This study investigated the effect of Jolly Phonics strategy on Jordanian first grade pupils' reading. Hence, the study followed a quasi- experimental research design. The participants of the study consisted of 58 first grade male and female pupils purposefully chosen from Al- Farouq School in Irbid city, Jordan. Based on the results of a reading pre- tests, two groups are assigned: an experimental group which consists of 29 pupils taught by using the Jolly Phonics strategy under study for five weeks, and a control group of 29 pupils taught by using the Conventional strategy suggested by Action Pack 1 Teacher's Guide, during the first semester of the academic year 2015-2016. In the current study, four instruments were used: a reading test, Jolly Phonics strategy worksheets, and Jolly Phonics songs with the Action Way. The findings of the study reported positive statistical effect of the strategy in focus.